A longitudinal study of the relation between creative potential and academic achievement at an engineering university in Korea. Issue 4 (9th October 2020) - Kim, Jin‐Young
Abstract: Background: Future scientists in engineering fields are expected, and even demanded, to be creative and innovative. Longitudinal studies pertaining to how creativity and academic achievement grow and develop over time remain limited. Purpose: This study examines (a) relationships between the creative potential of first‐year engineering students and their graduation grades as well as between the creative potential and graduation grades in nonmajor liberal arts courses, (b) the role of gender in creative potential, and (c) changes in creative potential after 4 years of college life. Method: In this exploratory study, the participants included 57 students from an engineering college in Korea. Data were first collected from 90 first‐year engineering students in August 2013. More than 4 years later in October 2017, 57 of these students were contacted again for follow‐up. Results: A positive relationship was found between the creative potential of engineering students and their academic achievement. Female students exhibited higher creative potential scores than the male students at both time points. Creative potential increased after 4 years, particularly in total creativity score, fluency, and originality. Conclusions: The findings from this study are different from the findings of Western engineering schools in their depiction of a positive relationship between creative potential and grades. This study indicated the possibility of developing creative potential even in adulthood. However, the results should be carefully interpreted not only because of the small sample size but also because of limitations of the Torrance Tests of Creative Thinking.